PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN TOMORO COFFEE SETIA BUDI KOTA MEDAN - Liana, Rika; Lestari, Indawati (Journal of Innovative and Creativity, 2026)
This study aims to determine the effect of product quality and service quality on purchasing decisions at Tomoro Coffee Setiabudi, Medan. The sample used in this study was purposive sampling, consisting of 98 respondents who had previously purchased products from Tomoro Coffee Setiabudi, Medan. Data analysis techniques used were descriptive and statistical analysis. Data collection methods included interviews, questionnaires, and documentation studies. The results showed that product quality and service quality simultaneously had a significant effect on purchasing decisions, with an F-value of 212.878 > F-table 3.09. The test conducted showed that product quality and service quality partially had a positive and significant effect on purchasing decisions. The Adjusted R-Square value obtained from the Coefficient of Determinant (R2) test on purchasing decisions was 0.814, meaning 81.4% can be explained by product quality and service quality. The remaining 18.6% can be explained by other factors not examined in this study.